The efficacy of fat-free mass index and appendicular skeletal muscle mass index in cancer malnutrition: a propensity score match analysis - Ji, Wei; Liu, XiangLiang; Liu, Pengfei; He, YuWei; Zhao, YiXin; Zheng, Kaiwen; Cui, JiuWei; Li, Wei (Frontiers in Nutrition, 2023)
Background: Reduced muscle mass (RMM) is a phenotypic criteria for malnutrition; 27 the appendicular skeletal muscle mass index (ASMI) and fat-free mass index (FFMI) 28 are both applicable indicators in the global leadership initiative on malnutrition 29 (GLIM) guideline. However, their sensitivity and prognostic effect remain unclear.30Methods: Clinical data of 2477 patients with malignant tumors were collected.Multi-frequency bioelectrical impedance analysis was used to obtain ASMI and FFMI.RMM was confirmed by ASMI (<7.0 kg/m² for men and <5.7 kg/m² for women) or 33 FFMI (<17 kg/m² for men and <15 kg/m² for women). Propensity score match 34 analysis and logistic regression analysis were used to evaluate the efficacy of FFMI 35 and ASMI in diagnosing severe malnutrition and multivariate Cox regression analysis 36 to determine the efficacy of RMM in predicting survival. Results: In total, 546 37 (22.0%) and 659 (26.6%) participants were diagnosed with RMM by ASMI 38 (RMM.ASMI group) and FFMI (RMM.FFMI group); 375 cases overlapped. Body 39 mass index (BMI), midarm circumference, triceps skinfold thickness, and maximum 40 calf circumference were all significantly larger in the RMM.FFMI group for both 41 sexes (P < 0.05). A 1:1 matched dataset constructed by propensity score match 42 contained 810 cases. RMM.FFMI was an influential factor of severe malnutrition with 43 HR = 3.033 (95% CI 2.068-4.449, P < 0.001) and RMM.ASMI was a predictive